Draw a Star and Make it Perfect: Incremental Processing of Telicity. Issue 10 (6th October 2021) - Foppolo, Francesca; Bosch, Jasmijn E.; Greco, Ciro; Carminati, Maria N.; Panzeri, Francesca
Abstract: Predicates like "coloring‐the‐star" denote events that have a temporal duration and a culmination point ( telos ). When combined with perfective aspect (e.g., "Valeria has colored the star"), a culmination inference arises implying that the action has stopped, and the star is fully colored. While the perfective aspect is known to constrain the conceptualization of the event as telic, many reading studies have demonstrated that readers do not make early commitments as to whether the event is bounded or unbounded. A few visual‐world studies tested the processing of telic predicates during online sentence processing, demonstrating an early integration of aspectual and temporal cues. By employing the visual‐world paradigm, we tested the incremental processing of the perfective aspect in Italian in two eye‐tracking studies in which listeners heard durative predicates in the perfective form in a scenario showing a completed and a non‐completed event. Differently from previous studies, we compared telic durative predicates such as "coloring‐the‐star" to punctual predicates such as "lighting‐the‐candle." While for punctual predicates, the inferences of telicity (the event has a telos) and of culmination (the telos is reached) are lexically encoded in the perfective verb, for durative predicates, the degree of event completion (visually encoded) needs to be integrated with perfective aspect (linguistically encoded) for the culmination inference derivation. By modulating the interaction of visual and linguistic stimuli across the two experiments, we show that the verb's perfective aspect triggers the culmination inference incrementally during sentence processing, offering novel evidence for the continuous integration of linguistic processing with real‐world visual information.